Utilização de características intrínsecas das redes de sensores sem fio na detecção de invasões - Paula, Luciano Bernardes de (2006)
The development of applications for Wireless Sensor Networks (WSNs) grows quickly and they are being applied to solve problems considered impossible before. The great challenge for the developers of solutions that use WSNs is how to deal with the resources limitation like the low battery capacity, low processing power and small amount of memory that the sensor nodes have. The increasing in the utilization of this kind of network, including military and civil applications, makes the security menaces to them increase as well. On the other hand, every security strategy already developed to conventional computers network cannot be applied to the WSNs, because of their limitations. The great part of the known attacks against WSNs is initiated by the invasion of the network by malicious sensor nodes, launched by the attacker inside the area of the network. Some approaches proposed in the literature seek to identify the attacks and not the invasion by the intruder nodes. This work has as goal to define attributes that can be inserted in the network layer protocols for WSNs giving to the network the ability of detect invasions by external nodes, independently of the attack that they would perform.